Tuning drop motion by chemical patterning of surfaces - Varagnolo, S (Langmuir : the ACS journal of surfaces and colloids, 2014)
We report the results of extensive experimental studies of the sliding of water drops on chemically heterogeneous surfaces formed by square and triangular hydrophobic domains printed on glass surfaces and arranged in various symmetric patterns. Overall, the critical Bond number, that is, the critical dimensionless force needed to depin the drop, is found to be strongly affected by the shape and the spatial arrangement of the domains. Soon after the droplet begins to move, stick-slip motion is observed on all surfaces, although it is less pronounced than that on striped surfaces. On the triangular patterns, anisotropic behavior is found with drops sliding down faster when the tips of the glass hydrophilic triangles are pointing in the down-plane direction. Away from the critical Bond number, the dynamic regime depends mainly on the static contact angle and weakly on the actual surface pattern. Lattice Boltzmann numerical simulations are performed to validate the experimental results and test the importance of the viscous ratio between the droplet phase and the outer phase